2008
DOI: 10.1128/jb.00974-08
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Mycobacterial Heparin-Binding Hemagglutinin with Actin, as Evidenced by Single-Molecule Force Spectroscopy

Abstract: Although Mycobacterium tuberculosis and related species are considered to be typical endosomal pathogens, recent studies have suggested that mycobacteria can be present in the cytoplasm of infected cells and cause cytoskeleton rearrangements, the mechanisms of which remain unknown. Here, we used single-molecule force spectroscopy to demonstrate that the heparin-binding hemagglutinin (HBHA), a surface adhesin from Mycobacterium tuberculosis displaying sequence similarities with actin-binding proteins, is able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Thus, the force values exerted by single adhesive bonds suggest that they could become sufficiently large to induce unfolding of a single KpOmpA. In addition to KpOmpA, other molecules (e.g., proteins or carbohydrates) can significantly contribute to bacterial adhesion and, thus, to the mechanical stress applied to the bacterial outer membrane (Alsteens et al, 2009;Aprikian et al, 2011;Verbelen et al, 2008;Yakovenko et al, 2008). It has been reported that the adhesion strength mediated by single bacterial proteins can reach sufficient values to induce the complete or partial unfolding of water-soluble proteins (Alsteens et al, 2009;Aprikian et al, 2011;Yakovenko et al, 2008).…”
Section: Possible Extension Of the Two-state Folding And Insertion Momentioning
confidence: 99%
“…Thus, the force values exerted by single adhesive bonds suggest that they could become sufficiently large to induce unfolding of a single KpOmpA. In addition to KpOmpA, other molecules (e.g., proteins or carbohydrates) can significantly contribute to bacterial adhesion and, thus, to the mechanical stress applied to the bacterial outer membrane (Alsteens et al, 2009;Aprikian et al, 2011;Verbelen et al, 2008;Yakovenko et al, 2008). It has been reported that the adhesion strength mediated by single bacterial proteins can reach sufficient values to induce the complete or partial unfolding of water-soluble proteins (Alsteens et al, 2009;Aprikian et al, 2011;Yakovenko et al, 2008).…”
Section: Possible Extension Of the Two-state Folding And Insertion Momentioning
confidence: 99%
“…Like other bacterial proteins, mycobacterial HBHA can mimic the function of some cellular proteins being responsible of the modification of diverse cellular activities, including entrance, survival and pathogen dissemination. Recent studies support this theory, Verbelen and collaborators reported that HBHA has a sequence similar to proteins that bound actin, like tropomiosin-1, ezrin-1 and the heavy chain of miosina-9, and their results demonstrated the specific and stable union of HBHA to actin (Verbelen et al, 2008). Another research group showed that HBHA was able to bind to G-actin without altering their nucleation but obstructing actin polymerization; these authors suggest that like profilin, HBHA can affect polymerizationdepolymerization dynamics of F-actin facilitating M. tuberculosis mobility into the cytoplasm (Esposito et al, 2011).…”
Section: Epithelial Cells Infection By M Tuberculosismentioning
confidence: 69%
“…Hence, HBHA-induced transcytosis provides a model for macrophage-independent extrapulmonary dissemination of Mtb that can lead to a more expansive systemic infection of the host [24]. Other studies have demonstrated that nanoscale distribution of the protein on the mycobacterial surface assessed by atomic force microscopy provided a fine mapping of HBHA distribution in nanodomains, which may effectively mediate adhesion to target cells, induce recruitment of receptors within membrane rafts [25,26] and therefore promotes Mtb transcytosis into the bloodstream.…”
Section: Structure-function I: the Functionally Important Cterminal Dmentioning
confidence: 97%
“…Since it has been shown that Mtb can escape from the phagosome and translocate into the cytosol, where they can be found in tightly packed clumps [8], it is possible that aggregation occurs during the intracellular lifestyle of Mtb, either within host cells or during transcytosis. It has even been suggested [26] that HBHA may interact with cytosolic components of the host cells such as actin. These preliminary observations, that require further experimental confirmation, open the possibility that HBHA belongs to the list of Mtb proteins directly involved in the interaction with cytosolic components, which is becoming a very important and previously neglected step of Mtb pathogenesis.…”
Section: An Integrated Modelmentioning
confidence: 98%